Effects of Spirulina platensis extract on serum Malondialdehyde (MDA) levels and differential leukocyte count on motor vehicle exhaust emissions exposure (in vivo study on Wistar rats) - Dea May Fitry; Nani Maharani; Renni Yuniati (Research Centre of Inorganic Materials and Complexs, 2020)
The particulate matter in vehicle emission has been shown to cause an increase in free radical levels which can increase serum MDA levels and leukocyte count. Spirulina platensis is an algae that has antioxidant effects that can scavenge free radicals. In this research, twenty-four of wistar mice are divided into 4 groups. Groups X1 and X2 received vehicle emission smoke exposure treatment and were given oral Spirulina platensis extract at a dose of 500 and 750 mg / kgBW / day for 14 days, the negative control group (C2) was given 0.9% NaCl orally and the normal control group did not get vehicle emission smoke exposure and Spirulina platensis extract. Serum MDA levels were checked by ELISA method and leukocyte count by giemsa staining. Data analysis was performed by using the one-way ANOVA test followed by Post Hoc Bonferroni. The results showed the mean serum MDA levels there was a significant difference between group C2 and group X2. In the mean absolute value of neutrophils and lymphocytes, there were significant differences between the C2 group with the administration of X1 and X2. In the mean absolute value of eosinophils and monocytes, there were significant differences between groups C1 and C2 and group X2 and between groups X1 and C1. Furthermore, the given doses of Spirulina platensis extract at a dose of 750mg / kgBW had an effect on serum MDA levels as well as the number of neutrophils and lymphocytes and the administration of doses of 500 and 750mg / kgBW affected the number of eosinophils and monocytes.